How a co-design process led to more contextually relevant family planning interventions in emerging urban settings in Eastern Uganda. - Jacquellyn Nambi Ssanyu; Rornald Muhumuza Kananura; Catherine Birabwa; Felix Kizito; Sarah Namutamba; Dorothy Akongo; Elizabeth Namara; Moses Kyangwa; Henry Kaula; Doreen Nakimuli; Andrew Magunda; Othman Kakaire; et al. (Public Library of Science (PLoS), 2023)
Voluntary, rights-based family planning upholds women's right to determine freely the number and spacing of their children. However, low-resource settings like Uganda still face a high unmet need for family planning. And, while urban areas are often indicated to have better access to health services, emerging evidence is revealing intra-urban socio-economic differentials in family planning utilization. To address the barriers to contraceptive use in these settings, understanding community-specific challenges and involving them in tailored intervention design is crucial. This paper describes the use of co-design, a human-centred design tool, to develop context-specific interventions that promote voluntary family planning in urban settings in Eastern Uganda. A five-stage co-design approach was used: 1) Empathize: primary data was collected to understand the problem and people involved, 2) Define: findings were shared with 56 participants in a three-day in-person co-design workshop, including community members, family planning service providers and leaders, 3) Ideate: workshop participants generated potential solutions, 4) Prototype: participants prioritized prototypes, and 5) Testing: user feedback was sought about the prototypes. A package of ten interventions was developed. Five interventions targeted demand-side barriers to family planning uptake, four targeted supply-side barriers, and one addressed leadership and governance barriers. Involving a diverse group of co-creators provided varied experiences and expertise to develop the interventions. Participants expressed satisfaction with their involvement in finding solutions to challenges in their communities. However, power imbalances and language barriers were identified by the participants as potential barriers to positive group dynamics and discussion quality. To address them, participants were separated into groups, and medical terminologies were simplified during brainstorming sessions. These changes improved participation and maximized the contributions of all participants. It is therefore important to consider participant characteristics and their potential impact on the process, especially when engaging diverse participant groups, and implement measures to mitigate their effects.